CURRENT ASPECTS OF THE AUDIT OF PUBLIC PROCUREMENT EFFICIENCY - Syrotiuk , Г.; Yankovska , К.; Zhydovska , Н. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
This study examines important aspects of the performance audit within the context of the public procurement system. Forms of government audit are analyzed according to the INTOSAI classification, substantiating that performance audit is the most valuable in improving the public sector's management process. This is because it helps understand how planning, execution, and cost control contribute to the achievement of strategic goals in the public procurement process. The essence of performance audit in public procurement is revealed, focusing on ensuring transparency, efficiency, and stability in financial resource management. This facilitates the optimal use of budgetary funds and the implementation of modern approaches to cash flow management for the benefit of the public. The principles of performance audit are presented to fully disclose its essence: economy, effectiveness, efficiency, environment, fairness, ethics, economic welfare, expediency, evolution, and a proposed addition of adaptability. It is noted that these principles in the context of public procurement allow for the identification and evaluation of resource utilization effectiveness and compliance with sustainability criteria in the supplier’s choice. The main stages of conducting the performance audit in public procurement are outlined, including audit planning, data collection, and analysis, compliance with rules and legislation, cost efficiency evaluation, assessment of the quality of goods and services, risk identification, report preparation, monitoring, and control. The peculiarities of conducting the performance audit considering the wartime situation in the country, are highlighted. Special attention is paid to the criteria for evaluating the sustainability of goods and services during public procurement. The essence of environmental, economic, and social criteria is analyzed.